Einleitung in die hellenistischjüdische literatur: apokrypha, pseudepigrapha und fragmente verlorener autorenwerke - Siegert, Folker (De Gruyter, 2016)
This is the first complete overview of all anonymous, pseudepigraphic, and fragmentary Greek textual sources handed down from ancient Judaism, including translations into Western or Eastern languages. Each text is described according to the rules of scholarly introduction and checked for its original language, authenticity, and literary genesis. Special attention is paid to Christian modifications. Folker Siegert, Institutum Judaicum Delitzschianum, University ofMünster, Germany.